AEGIS: The Color-Magnitude Relation for X-Ray-selected Active Galactic Nuclei - Nandra, K; Georgakakis, A; Willmer, C. N. A; Cooper, M. C; Croton, D. J; Davis, M; Faber, S. M; Koo, D. C; Laird, E. S; Newman, J. A (The Astrophysical journal, 2007)
We discuss the relationship between rest-frame color and optical luminosity for X-ray sources in the range 0.6< z <1.4 selected from the Chandra survey of the Extended Groth Strip. These objects are almost exclusively active galactic nuclei (AGNs). While there are a few luminous QSOs, most are relatively weak or obscured AGNs whose optical colors should be dominated by host galaxy light The vast majority of AGN hosts at z 6 1 are luminous and red, with very few objects fainter than M sub(B) = -20.5 or bluer than U-B = 0.6. This places the AGNs in a distinct region of color-magnitude space, on the "red sequence" or at the top of the "blue cloud," with many in between these two modes in galaxy color. A key stage in the evolution of massive galaxies is when star formation is quenched, resulting in a migration from the blue cloud to the red sequence. Our results are consistent with scenarios in which AGNs either cause or maintain this quenching. The large number of red-sequence AGNs implies that strong, ongoing star formation is not a necessary ingredient for AGN activity, as black hole accretion appears often to persist after star formation has been terminated.